Tradisi yang memudar: menyikapi hilangnya nilai budaya di kalangan generasi muda - Triyana, Angelia (Maliki Interdisciplinary Journal, 2025)
Fading traditions among the younger generation are becoming an increasingly pressing issue, especially in the context of preserving local cultural values. In this study, we analyze the various factors that lead to the loss of traditions, as well as the efforts that can be made to restore and strengthen these cultural values. The research shows that the integration of cultural values in the education system, community participation, and traditional art performances have proven effective in preserving culture. In addition, challenges, such as the influence of digital media and globalization, must be addressed with innovative and inclusive approaches. Awareness and knowledge of the importance of local culture must be instilled early in the younger generation so that they can appreciate and preserve the existing cultural heritage.